2014
DOI: 10.1016/j.jadohealth.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeper Training and Access to Mental Health Care at Universities and Colleges

Abstract: Purpose Gatekeeper-training programs (GKTs) are an increasingly popular approach to addressing access to mental health care in adolescent and young adult populations. This study evaluates the effectiveness of a widely used GKT program, Mental Health First Aid (MHFA), in college student populations. Methods A randomized control trial was conducted on 32 colleges and universities between 2009 and 2011. Campus residence halls were assigned to the intervention (MHFA plus preexisting trainings) or control conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 20 publications
2
96
0
Order By: Relevance
“…Other measures used were basic rating scales, for example a categorical measure of the number of residents with whom university resident advisors interacted [21]. None of the included studies undertook an economic evaluation or reported resource use or costs.…”
Section: Resultsmentioning
confidence: 99%
“…Other measures used were basic rating scales, for example a categorical measure of the number of residents with whom university resident advisors interacted [21]. None of the included studies undertook an economic evaluation or reported resource use or costs.…”
Section: Resultsmentioning
confidence: 99%
“…Davies, Beever, & Glazebrook, 2016;Lipson, Speer, Brunwasser, Hahn, & Eisenberg, 2014). However, as Lipson et al (2014) found, effects are not apparent for the translation of these improvements into help-seeking behaviours or mental health service utilisation among students.…”
Section: Evidence Base For Programs and Interventionsmentioning
confidence: 92%
“…However, most of the research was conducted in Australia, where the training was originally developed (8). There has been very little research on the impact of MHFA on MHL in the United States, with only two studies published thus far (9,10). Although the results of both studies were consistent with previous research, further evidence of the impact of MHFA on the American public in general, and among specific subgroups, is needed.…”
mentioning
confidence: 99%